INVESTMENT POTENTIAL OF THE INSURANCE SECTOR IN KAZAKHSTAN - Kalkabayeva Gaukhar; Iskakova Zagira; Rakhmetova Aibotа (Scientific Journal of Pedagogy and Economics, 2020)
The article presents the results of a study of investment opportunities of insurance companies in Kazakhstan to Finance the economy. The reasons for the insignificant investment potential of the Kazakh insurance sector, due to insufficient development of the insurance market, low level of equity of insurance organizations, are identified. It is necessary to reorient the investment strategy of insurance companies to Finance the national economy, which will have a positive impact on economic growth. Based on the analysis of the investment portfolio of insurance companies, it is concluded that there are high risks in the investment sphere, a lack of attractive investment projects and instruments, a limited list of securities for investment, and strict requirements of the regulator for financial stability. Combining a group of factors that affect the investment activity of insurance companies, as well as a SWOT analysis of the investment potential of the insurance sector, allowed us to formulate certain proposals for further improving the investment strategy of insurance companies, considering the goals of sustainable development of the financial system of Kazakhstan. The important role of state support for insurance organizations that make long-term investments in real sector enterprises is determined. The procedure for determining insurance companies that are actively investing in the innovative sector can be based on the application of coefficient analysis of investment investments of insurance companies. In addition, it is necessary to review the standards for the diversification of assets of insurance organizations with the development of unified rules for the placement of funds of insurance companies that restrict investment in the sphere of the national economy. The purpose of such regulations is to direct investment resources in the production sector, which must be developed in specific regions and in a specific time period.